STRATEGY OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN OVERCOMING STUDENTS' PSYCHOLOGICAL BARRIERS - M. Musa (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2021)
Learning strategies that emphasize the process of delivering material verbally from a teacher to a group of students with the intention that students can master the learning material optimally, Students are not required to find the material, Obstacles in learning occur due to human factors, namely teachers and participants students, institutional factors namely classrooms, and instructional namely lack of props.